IMPLEMENTASI STRATEGI PEMBELAJARAN SENTRA UNTUK GANGGUAN PSIKIS (EMOSI DAN SOSIAL) PADA ANAK USI DINI - Randi Purnama (Jurnal At-Tabayyun, 2019)
Center-based learning is a learning strategy that is performed within "circle times" and play centers. A circle is the moment when the teacher sits with the child in a circular position to give the child a foothold done before and after play. A play center is a child's play zone or area equipped with a set of play tools, which serves as a foothold of the treated environment to develop the entire basic potential of the protégé in various aspects of development in a balanced manner. In the center play there are three types of play, namely functional play, role playing, and constructive play. There are things to do in the play center, namely center play, classroom management, learning procedures, and assessment.psychic disorders experienced by early childhood namely emotional and social disorders. This type of emotional disorder is weak afection, anxiety, hypersensitivity, and phobia, and there are several factors that cause the problem of emotional disorders. The types of social disorders are maladjustment, egocentrism, isolated, aggressive child, negativism, quarrels, mocking and bullying, conscing behavior and prejudice and factors that result in the onset of the problem of social disorder.